PROGRAMAÇÃO DE UMA BASE DE DADOS PARA A ANÁLISE DE INFORMAÇÕES DE SEGURANÇA EM MÁQUINAS-FERRAMENTAS - Endruweit, Andreas A. B.; Schneider, Andresa; Eckhardt, Moacir; Ribeiro, Luis F. M.; Sackser, Gilberto; Duarte, Luiz C. S. (Salão do Conhecimento, 2013)
Resumo